E-Governance Projects: Current Status in Punjab - Kaur , Harpreet (Gyan Management Journal, 2016)
India is a developing country with a number of projects of e-Governance being implemented. I major challenge before the Government to successfully run them. There exist problems such as la awareness, low literacy, poverty, low network bandwidth issues and political scenario. This pa describes the significant projects implemented in India and current status of e-governance and fa of e-governance in Punjab. It also provides the suggestions for developing effective e-Govem projects, and concludes with a discussion of the most significant benefits of implementing such pro
Keywords: e-Governance; India; Significant; SMART